Experimental study on dynamic mechanical properties of projectile 155mm ERFB BT material - Ohol, Rajesh B.; Parshuramkar, Tekram N.; Parate, B. A.; Thakur, Dineshsingh G. (Defence Science Journal, 2023)
Artillery projectile 155mm high explosive (HE) extended range full bore boat tail (ERFB BT) and its components experience a high pressure loading of the propellant during gun launch. Mechanical properties of an engineering material are measured using quasi-static tensile test at room temperature. The materials of the projectile and its components are expected to survive time dependent propellant pressure loading inside the gun, which lasts for few microseconds. To investigate dynamic mechanical properties of the projectile and its components at medium strain rates and elevated temperature, the experimental analysis is undertaken. This research paper aims to examine the effect of medium strain rates and elevated temperatures on flow properties of the materials used in the projectile. The uniaxial tensile tests at the medium strain rates between 0.01 s-1 to 1s-1 and at elevated temperatures ranging between 150°C to 500°C are performed separately. The Considѐre criterion was applied to evaluate strain hardening exponent of the materials. Values of strain hardening exponents of shell body and boat tail materials are less than that of driving band material. Strain rate sensitivity of the materials is observed to be very low, thus indicating a good resistance to plastic deformation. The yield strength and true yield strength of the materials fall with increase in temperature.